THE OVERVIEW OF THE TECHNIQUES FOR TEACHING VOCABULARY - Evi Agustina Sari (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2010)
Having good vocabulary will help the students to understand English passages. A more general way to help students develop vocabulary is by fostering a word consciousness, an awareness of and interest words. Therefore, instruction in vocabulary involves far more than looking up word in a dictionary and using the words in a sentence. The English teacher should apply some techniques in teaching vocabulary  efficiently, successfully, interestingly, and enjoyably. To increase the students’ vocabulary may include choosing the  words in the reading passage and discussing them with the aspects of pronunciation, word form, dictionary work, reading, and using the words in context in five meetings. Other technique is assigning each student a word to look up and present in the class based on “word profile” in one meeting. And the last is practicing vocabulary through games with the whole class, in pairs or teams and in groups. These techniques can be applied to suit the proficiency level of the students and different teaching environments.